Thoughtload : manage the madness and free your team to do great work - Davey, Liane, 1972- (Page Two, 2026)
"Thoughtload-not workload-is the culprit causing chaos for your team. Be the leader that creates clarity, calm, and greater capacity. In Thoughtload, New York Times bestselling author and team effectiveness advisor Liane Davey tackles today's most pressing management challenges: over-burdened systems, burned-out teams, and declining results. However, contrary to conventional wisdom, Davey argues that the problem is not with out-sized workloads. The root cause of the madness sapping productivity in today's offices is with our excessive thoughtload. Thoughtload is the cumulative and often overwhelming burden of increasing cognitive and emotional demands, worsened by decreasing physical and mental energy. In this brilliant, highly prescriptive guide, Davey lays out the steps for reducing thoughtload, so that you and your team feel more focused-and get more done. The process starts with you. By learning to better manage your attention, you create periods of deep concentration that lead to the outcomes you strive for, and a sense of accomplishment. By processing emotions triggered in the workplace and at home, you gain greater control of your mood and productivity. And by making informed choices about where your energy comes from (and where it goes), you connect with reliable and renewable resources that fuel you to do the things that matter most. Davey then gives you powerful tools you can use as a leader to coach your team members to manage thoughtload for themselves. Doing so, you and your team will feel more focused, less burnt out, and finally free to do more great work. Backed by science and written with the time- and energy-strapped manager in mind, Thoughtload is Liane Davey's potent handbook for a better way to lead. Apply the strategies in this book to create calm within the chaos-so you and your team can perform, produce, and prosper."--